Modified Key Model of Data Encryption Standard - Mohammed Salih, Salih (Anbar Journal of Engineering Sciences, 2010)
This paper specifies a proposed improvement model of Data Encryption Standard (DES) which may be used to protect sensitive data. Protection of data during transmission may be necessary to maintain the confidentiality and integrity of the transformation represented by data. Instead of expansion step in each round which made by copying 16 bit from 32 bits data in each right side of the standard algorithm, the unused 8-bits as a key (sometimes it is used for error detection and correction purposes, or it is possible to generate an additional 8-bits with the 56-bits standard key) in the first starting round with the other 8-neglected bits from each of 16 round in the key algorithm will be used, and take the same locations of the expanded data. As a result, the complexity to cryptanalysis of the secured data has been increased. The proposed method was more active and reliable than standard conventional DES, where it can be switched to the system at any round for working with original DES algorithm, which means that an additional security has been added